Benefits that influence the usage of RFID technology in MPH Bookstore / Muhamad Rakesh Muhamad Hairi - Muhamad Hairi, Muhamad Rakesh (2014)
The purpose of this study is to examine factors that influence benefit of RFID in a company regarding on inventory management and information quality. This technology is widely used in other countries but not us. Hence, the implementation of RFID technology is needed to improve on inventory management and information quality in a company so that they will not left behind. Therefore, this research will be focused on the benefits of these two factors besides the role they play in a company. This research will find out whether these two factors plays important role in directly influence the benefits of RFID in a company. Then, the study has been conducted in MPH Bookstore Aeon Jusco, Seremban, Negeri Sembilan. Different background of respondents has been used in this study. Questionnaires in English that has been distributed to employees who work at MPH Bookstore. The researcher assumes 40 respondents to answer the questionnaires. The respondents were asked whether they agree that RFID implementation will influence inventory management and information quality in a company. Moreover, hypothesis of this study were tested using SPSS tools. The finding with overall result specified that the independent variable and dependent variable were excellent and the study supported the hypothesis of the study and were found to be significant related to purchase intention.